Upacara Adat Pemakaman Mengenang Leluhur (Ma’ Nene) di Toraja, Lembang Bululangkan Kecamatan Rinding Allo Toraja Utara - Rismayanti Rismayanti; Yosaphat Haris Nusarastriya (Universitas Pendidikan Ganesha, 2020)
This research has been conducted in Lembang Bululangkan Rinding Allo District. The purpose of this research is to find out and understand the perception of the Lembang Bululangkan community about the symbols used in the Ma 'nene ritual; to describe the ceremony process of the Ma'nene ritual in Lembang Bululangkan; to illustrate the influence of Christianity in ceremony process of the ritual Ma 'nene; to find out the values and norms are contained in ceremony process of Ma' nene rituals. The research method uses a qualitative descriptive. Data is collected by observation, interviews and documentation. From the results of the research, the people's perceptions about Ma'nene in have similarity, but the procedures for implementation are different. The goal of the Ma'nene by Aluk Todolo is to ask for blessings to the ancestors, while the goal of the Christians who do Ma'nene is to do / follow a custom that must be performed at a certain time. The meaning of Ma'nene for Aluk Todolo and the Christians have similarity, both of them have an affection for their relative that has passed away. The influence of Ma'nene on Christianity is actually not too conspicuous for Christians, however it bring a great influence for Aluk Todolo people, there is a change in applied regulations and ceremony process. Ma’ene contains value and norms, they are social values, religious values, cultural values, deliberation values, values of responsibility. In addition, the norm of decency, the religious, and norm of family are still maintained.This research has been conducted in Lembang Bululangkan Rinding Allo District. The purpose of this research is to find out and understand the perception of the Lembang Bululangkan community about the symbols used in the Ma 'nene ritual; to describe the ceremony process of the Ma'nene ritual in Lembang Bululangkan; to illustrate the influence of Christianity in ceremony process of the ritual Ma 'nene; to find out the values and norms are contained in ceremony process of Ma' nene rituals. The research method uses a qualitative descriptive. Data is collected by observation, interviews and documentation. From the results of the research, the people's perceptions about Ma'nene in have similarity, but the procedures for implementation are different. The goal of the Ma'nene by Aluk Todolo is to ask for blessings to the ancestors, while the goal of the Christians who do Ma'nene is to do / follow a custom that must be performed at a certain time. The meaning of Ma'nene for Aluk Todolo and the Christians have similarity, both of them have an affection for their relative that has passed away. The influence of Ma'nene on Christianity is actually not too conspicuous for Christians, however it bring a great influence for Aluk Todolo people, there is a change in applied regulations and ceremony process. Ma’ene contains value and norms, they are social values, religious values, cultural values, deliberation values, values of responsibility. In addition, the norm of decency, the religious, and norm of family are still maintained.Keywords: Ma 'Nene Traditional Ceremony, at Lembang BuluLangkan